Assessment of Groundwater Quality in the Semi-Arid Environment: Implications of Climate Change - Otman El Mountassir; Mohammed Bahir; Samir Hakimi; Turki kh. Faraj; Paula M. Carreira (Limnological Review)
The hydrogeochemical properties and evolution of groundwater in the Essaouira syncline basin in northwestern Morocco were investigated in this study, with a total of 447 samples during different campaigns (April 2017, May 2018, March 2019, and July 2020). These samples were analyzed for major ions and stable and radioactive water isotopes (δ2H, δ18O, and 3H). With decreasing rainfall from climate change in Morocco, it is crucial to assess the sustainability of groundwater reserves. This shortage leads to the degradation of water and soil quality. To ensure sustainable water management and preserve the environment in the study area, it is necessary to assess groundwater quality for drinking and irrigation, take precautions, and establish management plans. This study assessed groundwater quality using two water quality index methods (WQI and IWQI). Several natural processes control groundwater mineralization, including the dissolution of evaporite and carbonate minerals, cation exchange phenomena, evaporation, and seawater intrusion. According to the results obtained using the WQI method, all groundwater samples in the study area are generally of poor quality and must be treated before being used for domestic purposes. Based on the results obtained by the IWQI method, the samples are suitable for use as irrigation water, especially for plants resistant to high salinity concentrations. Stable isotope measurements (δ2H and δ18O) indicate that Atlantic precipitation continuously recharges the recharge areas of the Essaouira Basin. Thus, the low values of tritium (3H) in groundwater mean that the freshwater in the Essaouira Basin is ancient.